GAMBARAN HISTOLOGI FASE REMODELLING JARINGAN LUKA KRONIK KULIT MENCIT SETELAH PEMBERIAN PERLAKUAN PLASMA JET - Gela Setya Ayu Putri; Ali Ali; Nasruddin Nasruddin (Program Studi Teknologi Laboratorium Medik, 2022)
The medical aspect of plasma conceptually is concerned with the ability of plasma to produce biological molecules, such as RONS, which can be physically controlled through dose and behavior. RONS in micro concentrations was reported to have wound healing properties. The effect of a plasma jet on chronic skin wounds of mice on day 14 which theoretically included the remodeling phase has not been widely studied. The aim of the study was to calculate the number of inflammatory cells, fibroblasts, blood vessels, the percentage of re-epithelization, and the percentage of necrosis. Experimental research method with an analytic descriptive design. The results of microscopic observations showed that based on the number of inflammatory cells (round cells) data, the control group was significantly higher than the non-contact plasma (P<0.05). Based on the blood vessel count data, it was found that the control group was significantly higher (P<0.05) than the contact group, non-contact group and non-contact group. Based on the data on the number of fibroblasts, the results in contact-non-contact group were significantly (P<0, 05) higher than control group and plasma-contact group. Based on the data on the percentage of reepithelialization, the results were different in all treatment groups but not significant (P>0.05). Based on the data on the percentage of necrosis, the results were were different in all treatment groups but not significant (P>0.05).